Science Literacy Profile of Eleventh-Grade High School Students in Acid-Base - Mufidah, Nisaul; Ardhana, Ivan Ashif (J-PEK (Jurnal Pembelajaran Kimia), 2024)
The assessment conducted by PISA indicates that the science literacy rate of students in Indonesia occupies the lowest rank. One of the reasons is the lack of literacy-based assessments with multiple representations. This study aims to describe the profile of science literacy skills of eleventh-grade students on base acid material. The method used is descriptive quantitative, with the subject of the study being 62 students in XI grade who have acquired base acid matter. The instrument used is 10 elements of scientific literacy description with a multiple representation framework developed, with a high-reliability value of 0.795. The study results showed that the average literacy profile of science students reached 56.22%, which belongs to the middle category, with 5% of students entering the lower category, 27% in the high category, and 68% in the medium category. Students' access to indicators explaining scientific phenomena reached 52.29%, interpreting data and evidence scientifically reached 54.96%, and evaluating and designing scientific research reached 83.3%. Based on these data, eleventh-grade students have a moderate level of science literacy, with the highest access to the indicators to evaluate and design scientific research. This literacy of science needs to be enhanced through the provision of scientific literacy tools that apply multiple representations.